Languages Mapping Techniques Using Leaflet for Visualization of Dictionary Headwords - Manikanta, V (International Journal of Computer Sciences and Engineering, 2025)
Dictionaries are generally the listing of lexemes from the lexicon of one or more languages with arranging of alphabets grammatically. The dictionary provides information about definitions, pronunciations, usage, translation, etymologies, etc. The Indian Languages are classified into 121 languages from the included constituent eighth schedule 22 languages and non-eighth schedule 99 languages. From the 121 languages are classified into family groups of Indo-European, Dravidian, Austro-Asiatic, Tibeto-Burmese and Semito-Hamitic. Learning through multiple Indian languages in a single platform with visually is one of the big tasks in any of the field. Visualization of multiple languages easily represented the states, language and their meanings easily explored in the form of maps.